Surgical exclusion of postsurgical pseudoaneurysm of the ascending aorta - Ramachandra Barik; Amar Narayana Patnaik; Ravintula Venkata Kumar; Rudra Prasad Mohapatra; Vikas Medep; Lalita Nemani (Wolters Kluwer Medknow Publications, 2014)
Pseudoaneurysm of ascending aorta after cardiac surgery is rare in children. We report a case of successful surgical exclusion of ascending aortic pseudoaneurysm in a 15-year-old boy. The neck of the aneurysm was in close proximity to the right coronary artery (RCA).